Odpowiedzi

2010-03-29T21:30:22+02:00
A) 6x = 3
x=2
b) -3x = 7
x=-7/3
c) 2x = ⅕
x=0,1
d) 1,2x = 4,8
x=4
e) ⅓x = -5
x=-15
f) -⅗x = -5
x=25/3
g) ¾x = 4/9
x=16/27
h) 0,1x = -7
x=-70
2010-03-29T21:33:25+02:00
A) 6x = 3 /: 6
x = 3/6
x = 1/3

b) -3x = 7 /: (-3)
x = -7/3
x = -2 i 1/3

c) 2x = ⅕ /: 2
x = 1/5 x 1/2
x = 1/10
x = 0,1

d) 1,2x = 4,8 /: 1,2
x = 4

e) ⅓x = -5 / : 1/3
x = -5 x 3
x = -15

f) -⅗x = -5 / : (-3/5)
x = (-5) x (-5/3)
x = 25/3
x = 8 i 1/3

g) ¾x = 4/9 /: 3/4
x = 4/9 x 4/3
x = 16/27

h) 0,1x = -7 / : 0,1
x = (-7) : 1/10
x = (-7) x 10
x = -70
2010-03-29T21:34:48+02:00
A) 6x=3|:6
x=½
b) -3x = 7|:-3
x=-2⅓
c) 2x = ⅕|:2
x=¹/₁₀
d) 1,2x = 4,8|1,2
x=4
e) ⅓x = -5|⅓
x=-15
f) -⅗x = -5|: -³/₅
x=-8⅓
g) ¾x = 4/9|:¾
x=16/27
h) 0,1x = -7|:0,1
x=-70